Plant Nutritional Status Explains the Modifying Effect of Provenance on the Response of Beech Sapling Root Traits to Differences in Soil Nutrient Supply - Meller, Sonia; Frossard, Emmanuel; Spohn, Marie; Luster, Jörg (Frontiers in Forests and Global Change, 2020)
Forests dominated by beech (Fagus sylvatica L.) cover large parts of Europe where they occupy a broad ecological niche in terms of soil fertility. This indicates a large potential to adapt to different soil conditions over long time periods. Recent changes in tree mineral nutrition across Europe raise the question to what degree beech can acclimate to changing soil conditions in the short term. In this study, we aimed at assessing the plasticity of root traits and rhizosphere properties of young beech trees from populations, that are adapted to either high or low nutrient supply, when growing in soils differing in their fertility. We sampled beech saplings from two forest sites of contrasting nutrient supply, most distinctly in terms of phosphorus. We grew them for two years in rhizoboxes in mineral soil either from their own site or from the other site. We assessed the influence of the factors „plant origin“ and „current soil“ on root traits and rhizosphere properties. Fine root traits related to growth (biomass, length), architecture (branching) and morphology (diameter) responded strongly to the factor “current soil”. Provenance (factor “plant origin”) modified the response. The modifying effect was consistent with an influence of the plant status in those nutrients, which were not in sufficient supply in the soil. An additional genotypic difference in the sensitivity of the beech saplings to different soil nutrient supply could not be excluded. Fine root parameters normalized for length, mass or volume (root tip density and frequency, specific root length and area, root tissue density) did not differ among the treatments. Differences in percentage of mycorrhizal root tips and rhizosphere parameters related to phosphorus mobilization potential (pH, abundance of organic acid anions, phosphatase activity) were small and mainly determined by the “current soil”. Provenance had only a minor modifying effect, possibly due to differences in the ability of the plants to transfer carbon compounds from the shoot to the root and the fungal partner. Our results indicate a high plasticity of young beech trees to adapt their root system to different soil nutrient supply, thereby also taking into account internal nutrient reserves.